Microbiology proficiency testing in fish and fishery products: detection of Listeria monocytogenes and Salmonella spp. - Prakash Chandra Gupta
This paper presents the results of two proficiency testing (PT) rounds conducted by the Export Inspection Agency (EIA) Chennai laboratory in 2021 for food testing laboratories in India. The PT program was designed in accordance with ISO/TS 22117, a standard for proficiency testing in food microbiology, and targeted Listeria monocytogenes and Salmonella spp as the organisms of focus. The samples were found to be stable and recoverable during the analysis, and all PT sample packages were delivered to participant laboratories in good condition. The participant laboratories reported high sensitivity rates of 100% for PT round 061021 M and 96.49% for PT round 050721 M. The accuracy rate in PT round 061021 M was 91.89% and 92.10% in case of PT round 050721 M. However, there were some false positive and false negative results reported by some participant laboratories in both PT rounds, which may have been caused by operational errors or inconsistencies in analysis. During the PT round 061021 M, out of a total of 38 participant laboratories, five laboratories reported false positive results and one laboratory reported a false negative result. Similarly, during the PT round 050721 M, six laboratories reported false positive results which resulted in their results being deemed unsatisfactory.